Searching for Asian paradigms : contribution of youth to the promotion of social goals and cultural values in the development process - Itty,C.I (Editor) (Asian Cultural Forum on Development : Distributed by Suksit Siam, 1984)
Papers presented to Expert Group Meeting on the Contribution of Youth to the Promotion of the Social Goals and Cultural Values in the Development Process held at Chiengmai, Thailand, 26 October-2 November 1981.